Development of a spreadsheet based fuel cell simulator modeling 2d flow in a serpentine channel - Ainaa syahirah binti Ahmad Anuar (2023)
This thesis report the development of a spreadsheet-based fuel cell simulator: modeling two-dimensional (2D) flow in a serpentine channel to solve momentum equations using microsoft excel by applying semi-implicit method for pressure-linked equation (SIMPLE) algorithm.